Educação ambiental crítica: da formação as transformações socioambientais da caatinga em Coronel João Sá/BA pelo extrativismo de minérios - Souza, Raul Mauricio Aragão (2021)
The unbalanced society-nature relationship causes socio-environmental inequality, which is evident in man's unbridled appropriation of nature, bringing changes in the constitution of geographic spaces, whether biotic, abiotic and social, to the detriment of the generation of wealth in the face of the expropriation and degradation of natural assets. Therefore, the extraction of minerals is an activity with a high capacity for socio-environmental degradation and, in addition to this characteristic, there is a lack of inspection, which enhances the relationship of destruction of natural assets. This interference of man in the environment, brings an annihilation rate of many species in proportions many times higher than natural extinction. In this sense, Critical Environmental Education in schools is a way to discuss social and environmental problems. Meanwhile, the research aims to analyze the social and environmental impacts of mineral extraction in Coronel João Sá/BA, observing the conditions of workers and the potential for social and environmental degradation. This work analyzes an area of rock extraction in the municipality of Coronel João Sá, located in the northeast of the state of Bahia, a semiarid region with a concentration of igneous rocks from the crystalline shield of the geological unit of Borborema. In view of this, the systemic method was used to understand the integrated relationship between society/nature. Thus, the nature of the research is of a quali-quantitative nature, as both are complementary to obtain results. The following methodological procedures were used: bibliographical, documental and field research. The didactic product resulting from the work was a virtual communication environment for the broadcast of Documentary Video material generated during the research entitled “A Pedra dos Sonhos e das Necessidades”. It is concluded that the process of extracting minerals in the municipality requires regulation and organization of environmental licensing and inspection of the activity by the government, as there is a process of degradation of nature and precariousness of the worker, as well as the importance of the insertion of interdisciplinary activities in the study of the environment for a critical view of socioenvironmental problems. Thus, this research sought, from critical environmental education, to instigate social actors to think more carefully and reflectively about the socio-environmental problems arising from the extraction of minerals, in order for a change in values and social transformation to occur.